Actuators: Tension Pistons: Amplifying Piston Force Using Fluid‐Induced Tension in Flexible Materials (Adv. Funct. Mater. 30/2019). (23rd July 2019) - Li, Shuguang; Vogt, Daniel M.; Bartlett, Nicholas W.; Rus, Daniela; Wood, Robert J.
Abstract : In article number1901419, Shuguang Li, Daniela Rus, Robert J. Wood, and co‐workers propose a new concept for a tension‐driven piston. It utilizes a combination of flexible membrane materials and compressible rigid structures. In contrast to conventional pistons, the pressure‐induced tension forces in the membrane play a primary role in the tension pistons. The tension piston can outperform conventional pistons with greater force, higher power, and higher energy efficiency.